PENERAPAN MEDIA MONOPOLI UNTUK MENINGKATKAN PEMAHAMAN SISWA YANG KURANG MEMAHAMI DALAM MATERI DIAGRAM DI KELAS IV SD NEGRI 004 KEPENUHAN HULU - Nona Riswana (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
The purpose of this study was to see the imprvement of mathematics leaning outcmes, especilly thrugh the use of monopoly media. The subjects of this study were all fourth grade students of SD Negeri 004 Kepenuhan Hulu, totaling 31 students. Data collection was carried out through observation forms, written tests and documents. This research is a Classroom Action Research (PTK). The results showed that the mathematics learning outcomes of students, especially those using monopoly game media, increased from 55.55% in the frst cycle to 88.89% in the second cycle so that they met the expected success criteria. The use of Monopoly Game Media in mathematics larning can help students bcome more active in the larning process and train group colaboration.